Sliding member

By forming a plating layer between Zn-Ni alloy and polytetrafluoroethylene on the sliding member, the problem of easy peeling of the plating layer under high surface pressure is solved, and the peel resistance of the plating layer is significantly improved, ensuring the sintering resistance and corrosion resistance of the member.

CN119768567APending Publication Date: 2025-04-04NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380052288.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-07-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Under high surface pressure with a Hertz surface pressure gauge greater than 1.5 GPa, the coating of the sliding member is easy to peel off, resulting in a reduction in sintering resistance and corrosion resistance. The prior art has failed to effectively improve the peel resistance of the coating.

Method used

The plating layer containing the Zn-Ni alloy master phase and polytetrafluoroethylene (PTFE) was used, and the Ni content of the Zn-Ni alloy was 10.0 to 17.0 mass %, and the PTFE content was 6.5 to 21.0 mass %, so as to improve the hardness and peel resistance of the plating layer.

Benefits of technology

Under high surface pressure with a Hertz surface pressure gauge greater than 1.5 GPa, the peel resistance of the plating layer of the sliding member is significantly improved, avoiding the reduction of sintering and corrosion resistance caused by the peeling of the plating layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768567A_ABST
    Figure CN119768567A_ABST
Patent Text Reader

Abstract

Provided is a sliding member having excellent plating layer peeling resistance even when sliding at a high surface pressure greater than 1.5 GPa by a Hertz surface pressure meter. A sliding member (1) is provided with: a base material (2) including a sliding surface (20) that slides with another member; and a plating layer (3) disposed at least on the sliding surface (20). The plating layer (3) contains a parent phase (30) and polytetrafluoroethylene (31). The parent phase (30) is a Zn-Ni alloy containing 10.0 to 17.0 mass% of Ni, with the remainder being Zn and impurities. The content of polytetrafluoroethylene (31) in the plating layer (3) is 6.5-21.0 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a sliding member. Background Art

[0002] Sliding components are a general term for components that are at least partially in contact with other components and the contacted parts slide. Examples of sliding components are wheels and rails of trains, engine cylinders and pistons, crankshafts and connecting rods, tools used in drilling, saw blades, pulleys, gears, industrial screws, nuts, bearings, guide components, and molds. Sliding components slide repeatedly relative to other components.

[0003] There is a case where a plated layer is formed on the surface of a sliding member. The plated layer is, for example, an alloy plated layer. For example, Japanese Patent Publication No. 2014-228063 (Patent Document 1), Japanese Patent Publication No. 05-279772 (Patent Document 2), and Japanese Patent Publication No. 2013-032571 (Patent Document 3) propose sliding members having an alloy plated layer formed on the surface.

[0004] In the sliding component described in Patent Document 1, a tin-zinc alloy plating layer composed of tin and zinc is formed on the sliding surface. In the sliding component described in Patent Document 1, the thickness of the alloy plating layer is 10 to 25 μm. It is characterized in that the weight ratio of zinc to the total weight of tin and zinc in the alloy plating layer is 20 to 80%. Patent Document 1 records the following: According to this sliding component, even if the sliding of the sliding part is in a severe state, the wear amount can be suppressed, which can contribute to the long life of various machines.

[0005] The sliding member described in Patent Document 2 is formed with a plating layer containing, by weight, 10 to 35% Zn, 2 to 20% Pb, 1 to 10% Ni, 0.1 to 1% B (boron), and the remainder Cu and impurities. Patent Document 2 states that: Thus, a sliding member having excellent seizure resistance, wear resistance, and corrosion resistance can be obtained even under severe conditions of high speed and high temperature use.

[0006] The sliding component described in Patent Document 3 is characterized in that it comprises: a substrate having a metal surface; and a zinc alloy plating layer provided on the substrate. The zinc alloy plating layer has a chemical composition containing Ni: 2 to 8% and Mo: 0.1 to 3% by mass, with the remainder being Zn and impurities. The hardness of the zinc alloy plating layer is 150 to 350 Hv, and the thickness is 0.1 to 30 μm. Patent Document 3 states: Thus, it is possible to obtain a zinc alloy plating component that not only imparts excellent corrosion resistance to the substrate, but can also be used as a sliding component.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2014-228063

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 05-279772

[0011] Patent Document 3: Japanese Patent Application Publication No. 2013-032571 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] There is a sliding member that slides under a high surface pressure greater than 1.5GPa with a Hertzian surface pressure gauge. Such sliding members are, for example, wheels and guide rails of trains, and industrial screws. On the other hand, the coating formed on the sliding member due to sliding under the high surface pressure is easy to peel off. Moreover, there is a concern that if the coating peels off, the sintering resistance and corrosion resistance of the sliding member will decrease. Therefore, the peeling resistance of the coating is preferably also excellent when sliding under a high surface pressure greater than 1.5GPa with a Hertzian surface pressure gauge.

[0014] On the other hand, in Patent Documents 1 to 3, no research is conducted on the peeling resistance of the coating when sliding under a high surface pressure greater than 1.5 GPa in Hertzian surface pressure. For example, in paragraph 0029 of Patent Document 1, a sliding test is conducted at a surface pressure of 224 MPa. For example, in paragraph 0009 of Patent Document 2, a sliding test is conducted at a maximum load of 500 kgf / cm 2 Evaluation of sintering resistance. If the unit is converted to Pa, it becomes 0.049 GPa. In Patent Document 3, no sliding test is performed. Therefore, even if the techniques disclosed in Patent Documents 1 to 3 are used, there is a possibility that the peeling resistance of the coating cannot be improved when sliding under a high surface pressure greater than 1.5 GPa in Hertzian surface pressure.

[0015] An object of the present disclosure is to provide a sliding member having excellent resistance to peeling of a plating layer even when sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure.

[0016] Solutions for solving problems

[0017] The sliding member of the present disclosure comprises:

[0018] A substrate including a sliding surface that slides with other members; and

[0019] a coating, which is disposed at least on the sliding surface,

[0020] The coating contains a matrix and polytetrafluoroethylene,

[0021] The parent phase is a Zn-Ni alloy, wherein Ni of the Zn-Ni alloy is 10.0 to 17.0 mass %, and the balance is Zn and impurities,

[0022] The content of the polytetrafluoroethylene in the plating layer is 6.5 to 21.0 mass %.

[0023] Effects of the Invention

[0024] The sliding member of the present disclosure is excellent in the peeling resistance of the plating layer even when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a cross-sectional view of the sliding member of this embodiment.

[0026] Figure 2 This is a graph showing the relationship between the Ni content of the Zn—Ni alloy plating layer, the polytetrafluoroethylene (PTFE) content, and the peeling resistance of the Zn—Ni alloy plating layer when sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure.

[0027] Figure 3 This is a graph showing the relationship between the PTFE / Ni ratio and the peeling resistance of the Zn—Ni alloy plating layer during sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure.

[0028] Figure 4 This is a photograph of the plating layer of Test No. 10 in this example.

[0029] Figure 5 Yes Figure 4 The image is obtained by converting the photo into black and white. DETAILED DESCRIPTION

[0030] Hereinafter, the present embodiment will be described in detail with reference to the drawings. The same reference numerals are given to the same or corresponding parts in the drawings, and their description will not be repeated.

[0031] The present inventors have studied sliding members having excellent resistance to peeling of the plating layer even when sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure. As a result, the following findings have been obtained.

[0032] If the coating is destroyed when sliding under the high surface pressure of 1.5GPa with the Hertzian surface pressure gauge, the coating is peeled off from the surface of the base material. On the other hand, if the hardness of the coating is higher, the coating is not easily damaged when sliding. Therefore, the inventors of the present invention believe that if the hardness of the coating is improved, there is the possibility that the coating can be suppressed from peeling off even when sliding under the high surface pressure of 1.5GPa with the Hertzian surface pressure gauge.

[0033] In addition, if a coating containing zinc (Zn) is formed in the coating, the corrosion resistance of the sliding member is improved by sacrificial corrosion protection. Therefore, the coating containing Zn has been used for the sliding member so far. However, the hardness of Zn is relatively low. Therefore, the inventors of the present invention believe that even if a Zn coating is formed, the peeling resistance of the coating during sliding under a high surface pressure greater than 1.5 GPa in Hertzian surface pressure cannot be improved.

[0034] Among them, the Zn-Ni alloy of nickel (Ni) and the balance of Zn and impurities in the Zn-based alloy has a relatively high hardness. Therefore, the inventors of the present invention believe that if a coating is formed using Ni and a Zn-Ni alloy of the balance of Zn and impurities, the peeling resistance of the coating can also be improved when sliding under a high surface pressure greater than 1.5 GPa in Hertzian surface pressure. In this specification, the coating of Ni and the balance of Zn and impurities is referred to as a Zn-Ni alloy coating, or simply a coating.

[0035] It is known that the alloy phase of Zn-Ni alloy has η phase, γ phase and / or α phase according to the Ni content. η phase is Zn phase with Ni solid solution. γ phase is Ni 5 Zn 21 The α phase is a Ni phase in which Zn is solid-dissolved. It is known that when the Ni content is less than 10.0% by mass, the Zn-Ni alloy becomes a mixed phase of the η phase and the γ phase. It is known that when the Ni content is 10.0 to 17.0% by mass, the Zn-Ni alloy mainly contains the γ phase. It is known that when the Ni content is greater than 17.0% by mass, the Zn-Ni alloy becomes a mixed phase of the γ phase and the α phase. Among the η phase, the γ phase and the α phase, the hardness of the γ phase is the highest. Therefore, it is believed that if the Ni content in the parent phase of the Zn-Ni alloy plating is 10.0 to 17.0% by mass, the hardness of the Zn-Ni alloy plating is improved.

[0036] The inventors of the present invention have conducted further research and have found that, in the case of a Zn-Ni alloy plating layer containing 10.0 to 17.0% by mass of Ni, by making it contain 6.5 to 21.0% by mass of polytetrafluoroethylene (PTFE), the peeling resistance is also improved under a high surface pressure greater than 1.5 GPa in Hertzian surface pressure.

[0037] The inventors of the present invention conducted the following experiment. A steel plate with a length of 150 mm, a width of 100 mm, and a thickness of 0.8 mm was prepared. A Zn-Ni alloy coating was formed on the surface of the steel plate. The Zn-Ni alloy coating contains a matrix and polytetrafluoroethylene (PTFE). The matrix of the Zn-Ni alloy coating is a Zn-Ni alloy with Ni and the remainder being Zn and impurities. The peeling resistance of the Zn-Ni alloy coating was tested by changing the Ni content and PTFE content of the Zn-Ni alloy coating. The peeling resistance evaluation test was carried out under the following conditions. Apparatus: Adhesion sliding tester No. 7 manufactured by Kobelco Seisakusho Co., Ltd., sliding pressure head: SUJ2 steel ball with a diameter of 4.763 mm, load: 3 kgf (Hertzian surface pressure (average surface pressure): 1.56 GPa), sliding amplitude: 10 mm, sliding speed: 4 mm / s, temperature: 1 to 30°C, oiling: no. The sliding pressure head was slid under the above conditions. If the Zn-Ni alloy coating is not peeled off, the sliding resistance is low due to the sliding of the sliding head and the Zn-Ni alloy coating. If the Zn-Ni alloy coating is peeled off, the sliding resistance increases sharply due to the sliding of the sliding head and the steel plate. Therefore, the number of sliding times when the sliding resistance increases to more than 3 times the sliding resistance of the previous sliding is defined as the "number of sliding times when the Zn-Ni alloy coating peels off". The results of the peeling resistance evaluation test are shown in Figure 2 middle.

[0038] Figure 2 This is a graph showing the relationship between the Ni content of the Zn—Ni alloy plating layer, the polytetrafluoroethylene (PTFE) content, and the peeling resistance of the Zn—Ni alloy plating layer when sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure. Figure 2 The horizontal axis represents the Ni content of the parent phase of the Zn—Ni alloy plating layer in mass %. Figure 2 The vertical axis represents the PTFE content in the Zn-Ni alloy plating layer in mass %. Figure 2 In the figure, the white circles indicate that the number of sliding times at which the Zn-Ni alloy coating peeled off was more than 600. Figure 2 In the figure, the black circles indicate that the number of sliding times for the Zn-Ni alloy coating to be peeled off is less than 600 times.

[0039] Reference Figure 2, if it is within the range of satisfying the Ni content of 10.0-17.0 mass % and the PTFE content of 6.5-21.0 mass %, the Zn-Ni alloy coating does not peel off even if it is slid 600 times under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure. In other words, it is clear that if it satisfies the Ni content of 10.0-17.0 mass % and the PTFE content of 6.5-21.0 mass %, the peeling resistance of the Zn-Ni alloy coating is improved when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0040] The present inventors investigated the Vickers hardness of a Zn-Ni alloy plating layer containing PTFE and obtained the following findings.

[0041] [Table 1]

[0042]

[0043] Table 1 is a partial excerpt of the embodiments described later. Referring to Table 1, the hardness of the Zn-Ni alloy coating of test number 3 to 5 containing PTFE is lower than that of the Zn-Ni alloy coating of test number 15 not containing PTFE. Moreover, when comparing test number 4 and test number 5 with the same Ni content, if the PTFE content is increased, the hardness of the Zn-Ni alloy coating decreases. The Zn-Ni alloy coating of test number 15 not containing PTFE peeled off during 5 slidings. In contrast, the Zn-Ni alloy coating of test numbers 3 to 5 containing PTFE peeled off after more than 600 slidings. Based on the above results, the following completely different insights from the past were obtained: although the hardness of the Zn-Ni alloy coating is reduced due to the presence of PTFE, the peeling resistance is improved.

[0044] If it is above-mentioned Ni content and PTFE content, although the hardness of Zn-Ni alloy coating reduces, the reason that the stripping resistance of Zn-Ni alloy coating when sliding under the high surface pressure of 1.5GPa with Hertz surface pressure gauge is improved is still uncertain.But, when not containing PTFE, the stripping resistance when sliding under the high surface pressure of 1.5GPa with Hertz surface pressure gauge is lower.Thus, it is believed that PTFE contributes to the raising of the stripping resistance when sliding under the high surface pressure of 1.5GPa with Hertz surface pressure gauge.The inventors etc. consider as follows.When forming Zn-Ni alloy coating, internal stress is produced in Zn-Ni alloy coating.If internal stress is higher, Zn-Ni alloy coating is easy to peel off at the interface between Zn-Ni alloy coating and substrate when being endowed with external force.

[0045] On the other hand, in the initial stage of forming the Zn-Ni alloy coating, PTFE affects the adsorption of Zn ions to the steel sheet surface, and there is a possibility that the internal stress of the Zn-Ni alloy coating is reduced. As a result, the inventors of the present invention thought that if PTFE is included in the Zn-Ni alloy coating, the internal stress generated when the Zn-Ni alloy coating is formed is reduced, and the peeling of the Zn-Ni alloy coating can be suppressed.

[0046] The sliding member of the present embodiment completed based on the above findings has the following configuration.

[0047] [1] A sliding member comprising:

[0048] A substrate including a sliding surface that slides with other members; and

[0049] a coating, which is disposed at least on the sliding surface,

[0050] The coating contains a matrix and polytetrafluoroethylene,

[0051] The parent phase is a Zn-Ni alloy, wherein Ni of the Zn-Ni alloy is 10.0 to 17.0 mass %, and the balance is Zn and impurities,

[0052] The content of the polytetrafluoroethylene in the plating layer is 6.5 to 21.0 mass %.

[0053] [2] The sliding member according to [1], wherein:

[0054] The coating satisfies formula (1),

[0055] 0.85≤[PTFE] / [Ni]≤1.05 (1),

[0056] In formula (1), the content of the polytetrafluoroethylene in the coating layer in mass % is substituted for [PTFE], and the content of the Ni in the parent phase in mass % is substituted for [Ni].

[0057] [3] The sliding member according to [1] or [2], wherein:

[0058] The blackened area ratio in the surface of the plated layer is 30% or less.

[0059] [Sliding member]

[0060] Figure 1 2 is a cross-sectional view of the sliding member 1 according to the present embodiment. Figure 1 , a sliding component 1 includes a substrate 2 and a plating layer 3 .

[0061] [Base material]

[0062] The base material 2 includes a sliding surface 20 that slides with other components. Other components refer to other sliding components. The sliding component 1 slides on the sliding surface 20 and other sliding components. In addition, as described later, the sliding surface 20 is a surface formed on the base material 2, and the plating layer 3 is arranged on the sliding surface 20. Therefore, when the sliding component 1 of this embodiment slides with other components, the plating layer 3 is arranged between the sliding surface 20 and the other sliding components.

[0063] The substrate 2 is not particularly limited as long as it can be used as a sliding member 1 and is a member that can be plated. The substrate 2 is, for example, a wheel and a guide rail of a train, an engine cylinder and a piston, a crankshaft and a connecting rod, a tool in a drilling process, a saw blade, a pulley, a gear, an industrial screw, a nut, a bearing, a guide member, and a mold. The composition of the substrate 2 is not particularly limited. The substrate 2 can be composed of a single metal, or it can be composed of an alloy, or it can be formed with a coating on the surface. The substrate 2 is, for example, carbon steel, stainless steel, alloy steel, carbon steel with a coating, stainless steel with a coating, and alloy steel with a coating.

[0064] [Plating]

[0065] The plating layer 3 is disposed at least on the sliding surface 20. When the substrate 2 includes other surfaces in addition to the sliding surface 20, the plating layer 3 may be disposed only on the sliding surface 20 or on other surfaces in addition to the sliding surface 20.

[0066] The plating layer 3 contains a matrix 30 and polytetrafluoroethylene (PTFE) 31 .

[0067] [Chemical composition of the parent phase]

[0068] The parent phase 30 of the plating layer 3 is a Zn-Ni alloy, and the nickel (Ni) of the Zn-Ni alloy is 10.0-17.0 mass %, and the balance is zinc (Zn) and impurities. In other words, the parent phase 30 is a Zn-Ni alloy composed of 10.0-17.0 mass % Ni, 83.0-90.0 mass % Zn, and impurities. It is known that the Zn-Ni alloy of this composition mainly contains γ phase. In this case, the hardness of the Zn-Ni alloy plating layer is improved, and the peeling resistance of the plating layer 3 is also improved when sliding under a high surface pressure greater than 1.5 GPa in the Hertzian surface pressure gauge. The preferred lower limit of the Ni content of the parent phase 30 of the plating layer 3 is 10.3 mass %, more preferably 10.5 mass %, more preferably 10.8 mass %, and more preferably 11.0 mass %. The preferred upper limit of the Ni content of the parent phase 30 of the plating layer 3 is 16.5 mass %, more preferably 16.0 mass %, more preferably 15.0 mass %, and more preferably 14.0 mass %. Impurities are, for example, hydrogen (H), oxygen (O), and iron (Fe). There is a case where the impurities in the parent phase 30 of the plating layer 3 contain less than 1.0 mass % in total. In addition, the Ni content refers to the Ni content in the parent phase 30.

[0069] [Polytetrafluoroethylene]

[0070] Polytetrafluoroethylene (PTFE) 31 is a kind of 2 F 4 ) n A resin having a repeating unit. In this specification, PTFE31 refers to particles with polytetrafluoroethylene as the main component. Specifically, PTFE31 refers to particles with polytetrafluoroethylene as 98% by mass or more and the remainder as impurities. In other words, the PTFE31 contained in the coating 3 of the present embodiment is equivalent to polytetrafluoroethylene particles. The PTFE31 of the present embodiment is not particularly limited, and well-known polytetrafluoroethylene particles can be used. In addition, the size of PTFE31 is not particularly limited, for example, the particle size of PTFE31 can also be 0.1 to 2.0 μm, or 0.4 to 1.0 μm. In addition, the particle size of PTFE31 refers to the average particle size of PTFE31.

[0071] In the present embodiment, the content of PTFE31 in the coating 3 is 6.5-21.0 mass %. If the coating 3 is as follows, the peeling resistance during sliding under a high surface pressure greater than 1.5 GPa in the Hertzian surface pressure gauge is also improved: it contains a parent phase 30 of a Zn-Ni alloy and 6.5-21.0 mass % of PTFE31, wherein Ni of the Zn-Ni alloy is 10.0-17.0 mass %, and the balance is Zn and impurities. The preferred lower limit of the content of PTFE31 is 6.7 mass %, more preferably 6.9 mass %, more preferably 7.0 mass %, more preferably 7.5 mass %, and more preferably 8.0 mass %. The preferred upper limit of the content of PTFE31 is 20.5 mass %, more preferably 20.0 mass %, more preferably 19.5 mass %, more preferably 19.0 mass %, more preferably 18.5 mass %, more preferably 18.0 mass %, more preferably 17.5 mass %, and more preferably 17.0 mass %. In addition, the PTFE content refers to the PTFE content in the plating layer 3 .

[0072] [PTFE content to Ni content ratio]

[0073] The ratio of the PTFE content in the plating layer 3 to the Ni content in the matrix 30 is not particularly limited. However, it is preferred that the ratio satisfies the formula (1).

[0074] 0.85≤[PTFE] / [Ni]≤1.05(1)

[0075] In the formula (1), the content of PTFE 31 in the plating layer 3 in mass % is substituted for [PTFE], and the content of Ni in the parent phase 30 in mass % is substituted for [Ni].

[0076] Hereinafter, the ratio of the content of the PTFE 31 in the plating layer 3 in mass % to the content of the Ni in the matrix 30 in mass % is referred to as “PTFE / Ni ratio”. Figure 3 This is a graph showing the relationship between the PTFE / Ni ratio and the peeling resistance of the Zn—Ni alloy plating layer 3 during sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure. Figure 3 Obtained from the Examples described below. Figure 3 The vertical axis represents the number of sliding times at which the plating layer 3 peeled off in the peeling resistance evaluation test. Figure 3 The horizontal axis is the PTFE / Ni ratio of the coating 3. Figure 3, if the PTFE / Ni ratio is 0.85 or more and 1.05 or less, the peeling resistance of the coating 3 during sliding under a high surface pressure greater than 1.5 GPa in the Hertzian surface pressure gauge is further improved. The further preferred lower limit of the PTFE / Ni ratio is 0.88, and more preferably 0.90. The further preferred upper limit of the PTFE / Ni ratio is 1.03, and more preferably 1.00.

[0077] [Method for measuring the composition of the coating]

[0078] The composition of the coating 3 is measured in the following manner. A field emission electron probe microanalyzer (FE-EPMA) is used to analyze the surface of the coating 3 using energy dispersive X-ray spectroscopy (EDX). Specifically, the measurement magnification is set to 1000 times, and an electron beam with an accelerating voltage of 15 kV and an irradiation current of a maximum of 1 nA is irradiated to measure the intensity of the Kα line, and the counts of nickel (Ni), zinc (Zn), and fluorine (F) in the field of view are measured. The obtained F counts are converted into the content of F in mass %. The content of F in mass % is divided by the atomic weight of F and converted into the molar amount of F. CF is calculated based on the molar amount of F. 2 The content in mass % is set as the content in mass % of PTFE31. Thus, the content of PTFE31 in the coating 3 is obtained. The obtained Ni count is converted into the content in mass % of Ni. The obtained Ni content is the content of Ni relative to the entire coating 3. Therefore, the Ni content is converted into the Ni content of the parent phase 30 that does not contain PTFE31 relative to the coating 3. Thus, the Ni content in the parent phase 30 of the coating 3 is obtained.

[0079] The plating layer 3 may contain impurities. The impurities are, for example, selected from the group consisting of hydrogen (H), oxygen (O), and Fe. The total amount of impurities contained in the plating layer 3 is, for example, less than 1.0 mass %, more preferably less than 0.5 mass %. Thus, the plating layer 3 may also be a plating layer 3 composed of a parent phase 30, PTFE 31, and one or more impurities selected from the group consisting of hydrogen (H), oxygen (O), and Fe. The content of impurities may also be 0 mass %. Thus, the plating layer 3 may also be a plating layer 3 composed of a parent phase 30 and PTFE 31.

[0080] [Crystal structure of Zn-Ni alloy]

[0081] The parent phase 30 of the plating layer 3 is a Zn-Ni alloy, wherein the nickel (Ni) of the Zn-Ni alloy is 10.0 to 17.0 mass %, and the balance is zinc (Zn) and impurities. In this case, the parent phase 30 of the plating layer 3 includes a γ phase. The γ phase is a phase having a chemical formula of Ni 5 Zn 21, a phase of a crystal structure of a cubic crystal with a lattice constant α=0.890nm. There is a case where the parent phase 30 of the coating 3 includes an η phase. The η phase is a phase of a hexagonal crystal structure with a chemical formula of Zn, a lattice constant of a=0.267nm and c=0.495nm. There is a case where the parent phase 30 of the coating 3 includes an α phase. The α phase is a phase of a face-centered cubic crystal structure with a chemical formula of Ni and a lattice constant of a=0.352nm. Among the η phase, the γ phase and the α phase, the γ phase has the highest hardness. Therefore, it is preferred that the parent phase 30 of the coating 3 is a γ phase single phase.

[0082] [Method for determining the crystal structure of the parent phase of the coating]

[0083] The crystal structure of the parent phase 30 of the coating 3 is determined as follows. X-ray diffraction measurement is performed on the surface of the coating 3 under the following measurement conditions. The phase is determined by comparing the obtained measured data chart with the values ​​recorded on the ICDD (International Center for Diffraction Data) card.

[0084] ·Equipment: X-ray diffraction device

[0085] ·X-ray tube: Co-Kα line

[0086] Scanning range: 2θ=10~110°

[0087] Scanning interval: 0.02°

[0088] [Thickness of the plating layer]

[0089] The thickness of the coating 3 is not particularly limited. If the thickness of the coating 3 is 1.0 μm or more, durability can be stably obtained. If the thickness of the coating 3 is 60.0 μm or less, excessive manufacturing costs can be suppressed. Therefore, the thickness of the coating 3 is preferably 1.0 to 60.0 μm. The lower limit of the thickness of the coating 3 is more preferably 2.0 μm, more preferably 3.0 μm, more preferably 5.0 μm, more preferably 7.0 μm, and more preferably 10.0 μm. The upper limit of the thickness of the coating 3 is more preferably 55.0 μm, more preferably 50.0 μm, more preferably 45.0 μm, more preferably 40.0 μm, more preferably 35.0 μm, more preferably 30.0 μm, more preferably 25.0 μm, and more preferably 20.0 μm.

[0090] [Method for measuring the thickness of the coating]

[0091] The thickness of the coating 3 is measured as follows. The thickness of the coating 3 is measured at any four locations on the surface of the coating 3 using an eddy current phase type film thickness meter. The coating 3 is measured in accordance with ISO (International Organization for Standardization) 21968 (2005). The arithmetic mean of the measurement results of the four locations is set as the thickness of the coating 3.

[0092] [Blackening area ratio of the plated layer]

[0093] The result of the research of the present inventors, etc., clearly shows that there is the following situation: if the plating layer 3 as Zn-Ni alloy contains a large amount of PTFE31 of more than 6.5 mass %, black spots are generated on the surface of the plating layer 3. In this specification, "black spots" refer to the partial or complete discoloration of the surface of the plating layer 3 into black. The present inventors, etc. believe that if the black spots on the surface of the plating layer 3 can be suppressed, the appearance of the sliding member 1 is improved. In the sliding member 1 of the present embodiment, it is preferred that the blackening area rate in the surface of the plating layer 3 is less than 30%. In this case, even if the content of the PTFE31 in the plating layer 3 of the sliding member 1 is higher than 6.5 mass %, the appearance of the plating layer 3 is also excellent. The upper limit of the blackening area rate in the surface of the plating layer 3 is further preferably 20%, and further preferably 15%. The blackening area rate in the surface of the plating layer 3 can also be 0%.

[0094] In this embodiment, the blackened area ratio can be obtained by the following method. Specifically, a photograph of an area of ​​100 mm in length and 100 mm in width is taken from the surface of the coating 3 of the sliding member 1. The blackened area is determined from the obtained photograph, and the area ratio of the blackened area is obtained. In addition, a person skilled in the art should be able to determine the blackened area. In addition, the area ratio can also be obtained by binarizing the obtained photograph using image processing.

[0095] [Other structures]

[0096] As described above, the sliding member 1 of the present embodiment includes a substrate 2 and a plating layer 3 formed on a sliding surface 20 of the substrate 2. The sliding member 1 may include structures other than the substrate 2 and the plating layer 3. For example, as an upper layer of the plating layer 3 of the sliding member 1, another plating layer may be formed, a chemical conversion treatment layer may be formed, or a lubricating coating layer may be formed.

[0097] The sliding member 1 of the present embodiment can be suitable for use in sliding under a high surface pressure greater than 1.5 GPa using a Hertzian surface pressure gauge. However, the use of the sliding member 1 of the present embodiment is not limited to sliding under a high surface pressure greater than 1.5 GPa using a Hertzian surface pressure gauge. The sliding member 1 of the present embodiment can also be suitable for use in sliding under a surface pressure of less than 1.5 GPa using a Hertzian surface pressure gauge.

[0098] [Manufacturing method]

[0099] The method for manufacturing the sliding member 1 according to the present embodiment includes a preparation step and a plating layer forming step.

[0100] [Preparation process]

[0101] In the preparation step, a substrate 2 and a plating solution are prepared. As described above, the substrate 2 is not particularly limited as long as it is used as a sliding member 1 and is a material that can be plated. The plating solution contains zinc ions, nickel ions, PTFE31, and a solvent. The plating solution preferably contains zinc ions: 1 to 100 g / L, nickel ions: 1 to 100 g / L, and PTFE31: 1 to 50 g / L. The solvent is, for example, water. The plating solution may also contain other components. Other components are, for example, selected from the group consisting of a conductive aid (supporting electrolyte) and a surfactant. The conductive aid is selected from the group consisting of, for example, sodium sulfate, ammonium sulfate, and ammonium chloride. The surfactant is, for example, selected from the group consisting of a cationic, anionic, and nonionic surfactant.

[0102] [Plating layer forming process]

[0103] In the plating forming step, the plating layer 3 is formed by plating treatment. In the plating forming step, at least the sliding surface 20 in the substrate 2 is brought into contact with the plating solution. Thus, the plating layer 3 is formed on at least the sliding surface 20 of the substrate 2. The plating layer 3 is preferably formed by electroplating. In the electroplating, at least the sliding surface 20 in the above-mentioned substrate 2 is brought into contact with the plating solution and energized. The conditions for electroplating can be appropriately set. The conditions for electroplating are, for example, as follows: plating solution pH: 1 to 10, plating solution temperature: 10 to 70°C, current density: 1 to 100 A / dm 2 , and processing time: 0.1 to 90 minutes.

[0104] In order to suppress black spots on the surface of the plated layer 3, for example, plating is performed under the following conditions. In this case, the blackened area ratio of the surface of the plated layer 3 can be made 30% or less.

[0105] ·Ni in plating solution 2+ / Zn 2+ Molar ratio ≤1.5

[0106] ·Metal salt concentration in the plating solution (Ni 2+ and Zn 2+ Total)≤1.5M

[0107] PTFE concentration in plating solution ≤25g / L

[0108] · Plating solution temperature 57~65℃

[0109] · Plating solution pH 2~4

[0110] Plating solution flow rate (linear flow rate) 0.1~0.4m / sec.

[0111] Current density ≤3A / dm 2

[0112] [Substrate treatment process]

[0113] The above-mentioned manufacturing method can also include a substrate treatment process before the coating formation process as required. The substrate treatment process is, for example, pickling and alkali degreasing. In the substrate treatment process, oil and dirt attached to the sliding surface 20 of the substrate 2 are removed. It can also be that the substrate treatment process also includes grinding processes such as sandblasting and mechanical grinding finishing. These substrate treatments can only be implemented in one way, or a plurality of substrate treatments can be combined and implemented.

[0114] The sliding member 1 of this embodiment is manufactured by the above steps. However, the above-mentioned method for manufacturing the sliding member 1 of this embodiment is only an example of the method for manufacturing the sliding member 1 of this embodiment, and is not limited to this manufacturing method. The sliding member 1 of this embodiment may also be manufactured by other methods.

[0115] Example

[0116] The effects of the sliding member of this embodiment will be further specifically described below using examples. The conditions in the following examples are one example of conditions used to confirm the feasibility and effects of the sliding member of this embodiment. Therefore, the sliding member of this embodiment is not limited to this one example of conditions.

[0117] In the examples, a plating layer with different compositions was formed on a steel sheet, and the peeling resistance of the plating layer during sliding under a high surface pressure exceeding 1.5 GPa in Hertzian surface pressure was evaluated. Specifically, the evaluation was performed as follows.

[0118] [Preparation process]

[0119] In this embodiment, a commercially available cold-rolled steel sheet is used as a substrate. The cold-rolled steel sheet is 150 mm long, 100 mm wide, and 0.8 mm thick. The steel type is SPCC (low carbon steel) specified by Japanese Industrial Standard (JIS) G3141 (2021). A plating is applied to the surface of the cold-rolled steel sheet in an area of ​​100 mm long by 100 mm wide.

[0120] The plating solution is an aqueous solution containing 100 to 250 g / L zinc sulfate heptahydrate, 150 to 350 g / L nickel sulfate hexahydrate, 75 g / L sodium sulfate, and 0 to 25 g / L polytetrafluoroethylene (PTFE), with a pH of 2 to 4. The metal salt concentration (Ni 2+ and Zn 2+ The total amount) is less than 1.5M. The composition of the plating solution is changed within the above range to form a coating on the steel plate of each test number. As a result, the composition of the coating of each test number is changed. In addition, in test numbers 16 to 18, the plating solution does not contain PTFE, but instead contains 3 to 10 g / L of graphite. The coating is formed by electroplating. The plating conditions are as follows: plating solution temperature: 50 to 60°C, current density: 1 to 10 A / dm 2 , Plated anode (counter electrode): titanium plate coated with iridium oxide. In this embodiment, as PTFE, particles with an average particle size of 0.4 to 1.0 μm, polytetrafluoroethylene of 98% by mass or more and the remainder being impurities are used.

[0121] In addition to the above conditions, test numbers 1 to 5 and 7 to 9 also satisfy the following conditions.

[0122] ·Ni in plating solution 2+ / Zn 2+ Molar ratio ≤1.5

[0123] · Plating solution temperature 57~60℃

[0124] Plating solution flow rate (linear flow rate) 0.1~0.4m / sec.

[0125] Current density ≤3A / dm 2

[0126] Test No. 6 was plated under the following conditions.

[0127] ·Ni in plating solution 2+ / Zn 2+ Molar ratio = 3.0

[0128] Plating solution temperature 50°C

[0129] Plating solution flow rate (linear flow rate) 0m / sec.

[0130] Current density ≤3A / dm 2

[0131] Test No. 10 was plated under the following conditions.

[0132] ·Ni in plating solution 2+ / Zn 2+ Molar ratio = 3.0

[0133] · Plating solution temperature 57~60℃

[0134] Plating solution flow rate (linear flow rate) 0.5m / sec.

[0135] Current density 6A / dm 2

[0136] [Test for measuring the composition of the plating layer]

[0137] The composition of the coating of each test number was measured in the following method. The surface of the coating of each test number was analyzed by energy dispersive X-ray spectroscopy (EDX) using a JXA-8530F field emission electron probe microanalyzer (FE-EPMA) manufactured by JEOL Ltd. Specifically, an electron beam with a measurement magnification of 1000 times, an acceleration voltage of 15 kV, and an irradiation current of a maximum of 1 nA was used to measure the intensity of the Kα line, and the counts of nickel (Ni), zinc (Zn), and fluorine (F) in the field of view were measured. The obtained F counts were converted to the content of F in mass %. The content of F in mass % was divided by the atomic weight of F to convert it to the molar amount of F. CF was calculated based on the molar amount of F. 2 The content of PTFE in mass % is defined as the content of PTFE in mass %. Thus, the content of PTFE in the coating layer is determined. The results are shown in the column "PTFE content (mass %)" in Table 2.

[0138] The obtained Ni count is converted into the Ni content in mass %. The obtained Ni content is the Ni content relative to the entire coating. Therefore, the Ni content is converted into the Ni content relative to the parent phase of the coating that does not contain PTFE. Thus, the Ni content in the parent phase of the coating is obtained. The results are shown in the "Ni content (mass %)" column of Table 2. The parent phase of the coating of each test number is Ni shown in Table 2 and the balance is Zn and impurities in the Zn-Ni alloy. In Table 2, the "[PTFE] / [Ni]" column shows the ratio of the content of PTFE in the coating in mass % to the content of Ni in the parent phase in mass %. In addition, in test number 15, the coating does not contain PTFE. In test numbers 16 to 18, the coating does not contain PTFE, but instead contains graphite. For test numbers 16 to 18, the content of graphite is shown in the "PTFE content (mass %)" column of Table 2.

[0139] [Table 2]

[0140]

[0141] [X-ray diffraction measurement test of the matrix of the coating]

[0142] The crystal structure of the parent phase of the coating of each test number was determined by the following method. The surface of the coating was measured by X-ray diffraction under the following measurement conditions. The phase was determined by comparing the obtained measured data chart with the value recorded on the ICDD card. As a result, in all examples, the parent phase of the coating contained a γ phase. The parent phase of the coating of test numbers 1, 4 to 6 and 10 was only a single γ phase.

[0143] · Equipment: X-ray diffraction equipment RINT-2500 manufactured by Rigaku Corporation

[0144] ·X-ray tube: Co-Kα line

[0145] Scanning range: 2θ=10~110°

[0146] Scanning interval: 0.02°

[0147] [Measurement test of coating thickness]

[0148] The thickness of the coating of each test number was measured as follows. The thickness of the coating was measured at any four locations on the surface of the coating using an eddy current phase thickness meter PHASCOPEPM910 manufactured by Helmut Fischer GmbH. The coating was measured in accordance with ISO 21968 (2005). The arithmetic mean of the measurement results of the four locations was set as the thickness of the coating. The results are shown in the column "Thickness of coating (μm)" in Table 2.

[0149] [Peeling resistance evaluation test]

[0150] The peeling resistance evaluation test of the coating was carried out on the steel plates with coating of each test number. The peeling resistance evaluation test of the coating was carried out under the following conditions. Apparatus: Adhesion sliding tester No. 7 manufactured by Kobelco, Ltd., sliding pressure head: SUJ2 steel ball with a diameter of 4.763 mm, load: 3 kgf (Hertz surface pressure (average surface pressure): 1.56 GPa), sliding amplitude: 10 mm, sliding speed: 4 mm / s, temperature: 1-30°C, oiling: none. The number of slides when the sliding resistance is increased to more than 3 times the sliding resistance of the previous slide is defined as "the number of slides when the coating peels off". The results are shown in the column "Number of slides when the coating peels off (times)" in Table 3.

[0151] [Table 3]

[0152]

[0153] [Blackening area ratio measurement test]

[0154] The blackened area ratios of the surfaces of the plated layers of Test Nos. 1 to 15 were measured in the following manner: A photograph was taken of the entire region of 100 mm in length and 100 mm in width where the plated layer was formed. Figure 4 This is a photograph of the plated layer of Test No. 10. The obtained photograph was converted into black and white by image processing. Figure 5 Yes Figure 4 The image was obtained by converting the photograph into black and white. The area ratio of the black portion to the entire area was calculated from the black and white binary image. The results are shown in the column "Blackened area ratio (%)" in Table 3.

[0155] [Hardness measurement test of coating]

[0156] The hardness of the coating was measured for test numbers 3 to 5 and 15. The hardness measurement test of the coating was carried out under the following conditions. The Vickers hardness (Hv) of the coating surface was measured using a microhardness tester FISCHERSCOPE (registered trademark) HM2000 manufactured by Helmut Fischer GmbH. The load was 10 to 50 mN. The load was adjusted so that 6 times the indentation depth (μm) was less than the coating thickness. The results are shown in the "Hardness (Hv) of the coating" column of Table 3.

[0157] [Evaluation results]

[0158] Referring to Tables 2 and 3, the coatings of test numbers 1 to 10 include a parent phase of a Zn-Ni alloy and PTFE having a content of 6.5 to 21.0 mass % in the coating, wherein Ni of the Zn-Ni alloy is 10.0 to 17.0 mass %, and the balance is Zn and impurities. As a result, in the peeling resistance evaluation test, the number of sliding times when the coating peels off is more than 600 times. It can be seen that the sliding components having the coatings of test numbers 1 to 10 have excellent peeling resistance when sliding under a high surface pressure greater than 1.5 GPa in the Hertzian surface pressure gauge.

[0159] Moreover, for test numbers 7 to 9 in which the PTFE / Ni ratio was 0.85 or more and 1.05 or less, the number of sliding times when the plating was peeled off in the peeling resistance evaluation test was 2000 or more. It can be seen that the sliding members having the plating of test numbers 7 to 9 were more excellent in the peeling resistance of the plating when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure compared with test numbers 1 to 6 and 10.

[0160] The blackened area ratio of the plating surface of test numbers 1 to 5 and 7 to 9 is 30% or less. It can be seen that the sliding members having the plating of test numbers 1 to 5 and 7 to 9 are excellent in the peeling resistance of the plating when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure, as compared with test numbers 6 and 10, and the appearance of the plating is excellent even when the PTFE content in the plating is as high as 6.5% or more.

[0161] On the other hand, the PTFE content of the coating of test number 11 was too low. As a result, in the peeling resistance evaluation test, the number of sliding times when the coating peeled off was less than 600 times. It can be seen that the sliding component having the coating of test number 11 cannot improve the peeling resistance of the coating when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0162] The Ni content and PTFE content of the plating layer of test number 12 were too low. As a result, the number of sliding times when the plating layer was peeled off in the peeling resistance evaluation test was less than 600 times. It can be seen that the sliding component having the plating layer of test number 12 cannot improve the peeling resistance of the plating layer when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0163] The Ni content of the plating layer of test number 13 was too low. As a result, in the peeling resistance evaluation test, the number of sliding times when the plating layer peeled off was less than 600 times. It is known that the sliding component having the plating layer of test number 13 cannot improve the peeling resistance of the plating layer when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0164] The Ni content of the plating layer of test number 14 was too high. As a result, in the peeling resistance evaluation test, the number of sliding times when the plating layer peeled off was less than 600 times. It is known that the sliding component having the plating layer of test number 14 cannot improve the peeling resistance of the plating layer when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0165] The plating layer of test number 15 does not contain PTFE. As a result, in the peeling resistance evaluation test, the number of sliding times when the plating layer peels off is less than 600 times. It is known that the sliding component having the plating layer of test number 15 cannot improve the peeling resistance of the plating layer when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0166] The plating layers of test numbers 16 to 18 contained graphite instead of PTFE. As a result, in the peeling resistance evaluation test, the number of sliding times when the plating peeled off was less than 600 times. It is known that the sliding components having the plating layers of test numbers 16 to 18 cannot improve the peeling resistance of the plating layers when sliding under a high surface pressure of more than 1.5 GPa in Hertzian surface pressure.

[0167] The embodiments of the present invention have been described above. However, the above embodiments are merely examples for implementing the present invention. Therefore, the present invention is not limited to the above embodiments, and can be implemented by appropriately changing the above embodiments without departing from the gist thereof.

[0168] Description of Reference Numerals

[0169] 1. Sliding component; 2. Base material; 20. Sliding surface; 30. Matrix; 31. Polytetrafluoroethylene (PTFE).

Claims

1. A sliding member comprising: A substrate including a sliding surface that slides with other members; and a coating, which is disposed at least on the sliding surface, The coating contains a matrix and polytetrafluoroethylene, The parent phase is a Zn-Ni alloy, wherein Ni of the Zn-Ni alloy is 10.0 to 17.0 mass %, and the balance is Zn and impurities, The content of the polytetrafluoroethylene in the plating layer is 6.5 to 21.0 mass %.

2. The sliding member according to claim 1, wherein: The coating satisfies formula (1), 0.85≤[PTFE] / [Ni]≤1.05 (1), In formula (1), the content of the polytetrafluoroethylene in the coating layer in mass % is substituted for [PTFE], and the content of the Ni in the parent phase in mass % is substituted for [Ni].

3. The sliding member according to claim 1 or 2, wherein: The blackened area ratio in the surface of the plated layer is 30% or less.

Citation Information

Patent Citations

  • Wear resistant sliding alloy, sliding member, and their production

    JP1993279772A

  • Sliding member comprising member plated with zinc alloy, and zinc alloy electroplating solution

    JP2013032571A

  • Sliding member, retainer, and rolling bearing

    JP2014228063A